Showing Your Value - Redish, Janice (Language at Work - Bridging Theory and Practice, 2007)
Amongst my fellow technical communicators and usability specialists, I often hear complaints that we don’t receive the respect we deserve. I hear worries about being underpaid for our contributions and being exploited internationally.